Innovative SAP SuccessFactors recruiting a guide to creating custom integration and automation - Athanur, Anand; Ingram, Mark; Wellens, Michael (Apress, 2022)
Get creative and optimize your SAP SuccessFactors Recruiting implementation with this guide, which examines a variety of integration and automation opportunities throughout the recruiting process outside of the standard integrations. Innovative SAP SuccessFactors Recruiting walks you through the end-to-end recruiting process and highlights opportunities to create interfaces and automation at each stage using a variety of methods and tools. After a brief overview of the market demands driving growth in this area and an introduction to OData, Anand Athanur, Mark Ingram and Michael A. Wellens detail each step in the recruiting process, starting with automating and integrating requisition creation using APIs and middleware. They then explore ways of enhancing candidate attraction and experience for the initial application process. After that, they jump into automation for overall candidate selection and processing, including automation using Robotic Process Automation, Integration center, the assessment integration framework, custom OData integrations, the background check integration framework, and Business Rules. Additionally, you'll be shown onboarding optimization techniques using Intelligent Services, as well as hiring into third-party HRIS systems. After finishing this book, you will have a thorough understanding of how to utilize SAP SuccessFactors to recruit the right candidates for every position. What You Will Learn Integrate and automate the requisition creation process in innovative ways outside of SAP documentation Enhance candidate attraction and experience Leverage integration and automation opportunities within the application processing stage Automate hiring into third-party HRIS systems Who this Book For Customers, Consultants, and 3rd Party Vendors wishing to connect their solutions to SAP SuccessFactors Recruiting.
Online resource; Title from title page (viewed November 30, 2021)
Keywords: SuccessFactors (Firm); SAP ERP; Personnel management -- Information technology; Employees -- Recruiting -- Data processing; Personnel management -- Data processing; Personnel; Direction; Technologie de l'information; Personnel; Recrutement; Informatique; Personnel; Direction; Informatique; Personnel management; Data processing